2010
DOI: 10.4103/0970-2113.71956
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokines in Egyptian elderly with chronic obstructive pulmonary disease

Abstract: Background:The pulmonary component of chronic obstructive pulmonary disease (COPD) is characterized by airflow limitation that is not fully reversible. The airflow limitation is usually progressive and associated with an abnormal inflammatory response of the lung to noxious particles or gases.Hypothesis:The levels of the proinflammatory cytokines, interleukin 1 beta (IL-1β), tumor necrosis factor alfa (TNF-α), and C-reactive protein (CRP), in elderly patients suffering from COPD are increased.Settings and Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…
FIGURE 2: Meta-analysis of 17 studies that investigated the association between serum C-reactive protein concentration and chronic obstructive pulmonary disease (COPD). 1127 CI, confidence interval
…”
Section: Resultsmentioning
confidence: 99%
“…
FIGURE 2: Meta-analysis of 17 studies that investigated the association between serum C-reactive protein concentration and chronic obstructive pulmonary disease (COPD). 1127 CI, confidence interval
…”
Section: Resultsmentioning
confidence: 99%
“… The prescribed medication was administered (Bronchodilators and/or Expectorants), and a cup of warm fluid was given if needed (8) .…”
Section:  An Arterial Blood Gases Analysismentioning
confidence: 99%
“…In 2005, three million deaths due to the disease were reported, and the WHO predicts that, by the year 2030, COPD will become the third leading cause of death (6,7) . Alexandria Main University Hospital, statistical reports showed that, 1645 patients were admitted to the Medical Chest Disease Department throughout the year of 2010, and COPD patients represented about one fifth of total admission rate (293 male and 72 female) (8,9) . Cigarette smoke has several direct effects on the respiratory tract, its irritating effects can cause hyperplasia of the cells including goblet cells which subsequently results in increased production of mucus and hyperplasia which reduces airway diameter and increases the difficulty in cleaning secretions.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there were no difference in TNF-and its antagonists in COPD patients compared with controls. A case control trial in Egyptian subjects over 60 years compared 3 groups of 30 subjects matched by age and sex, consisting of healthy subjects, COPD without any comorbidities, and COPD with cardiovascular disease but no other comorbidities (Amer, M.S., et al, 2010). There was no significant difference in the serum levels of IL-1 , TNF-, or C reactive protein (CRP) between the control subjects and the COPD subjects with no cardiac disease.…”
Section: Role Of Inflammatory Mediators and Cytokines In Protease-antmentioning
confidence: 99%